2002
DOI: 10.1080/1025814021000036115
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Tumor Markers in Cervical Cancer Patients

Abstract: Cervical carcinoma is the second most common cancer worldwide. The extent of free radical induced oxidative stress can be exacerbated by the decreased efficiency of antioxidant defense mechanisms. Low levels of essential antioxidants in the circulation have been found to be associated with an increased risk of cancer. The aim of our study was to assess the extent of oxidative stress, the levels of antioxidants like superoxide dismutase (SOD), catalase (CAT), ceruloplasmin and to evaluate tumor markers such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 0 publications
0
33
0
1
Order By: Relevance
“…[13][14][15][16] In the present study, we found significant association between oxidative stress parameters and sialoglycoproteins. In carcinoma prostate, lipid peroxides and protein carbonyls were positively correlated with PSA and protein-bound sialic acid.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…[13][14][15][16] In the present study, we found significant association between oxidative stress parameters and sialoglycoproteins. In carcinoma prostate, lipid peroxides and protein carbonyls were positively correlated with PSA and protein-bound sialic acid.…”
Section: Discussionmentioning
confidence: 61%
“…[13][14][15][16] Pasquale et al 17 demonstrated an association between lipid peroxides and PSA. Although oxidative stress and increase in sialoglycoprotein level and/or sialic acid content are reported in Ca prostate separately; however there are no reports correlating oxidative stress with sialylation parameters in both BPH and Ca prostate.…”
Section: Introductionmentioning
confidence: 99%
“…The increased serum sialic acid level in tumour patients has been explained by a spontaneous release (shedding) of aberrant sialic acid-containing cell surface glycoconjugates. 39) On drug treatment, glycoprotein component levels were reverted back to near normal levels. This could be due to the cytostabilizing property of KA as it contains SA and EO as its principle components.…”
Section: Resultsmentioning
confidence: 99%
“…Se considera mediador del daño vascular de enfermedades cardiovasculares como hipertensión, ateroesclerosis e isquemiareperfusión 21 . Su presencia se asocia también con varios tumores, como próstata 22 , cuello uterino 23 , ovario 24 y de hígado 25 .…”
Section: Toxicidad De Hierro Y Cobre Es Mediada Por Estrés Oxidativounclassified